KEKERASAN TERHADAP PEREMPUAN DALAM TAYANGAN SINETRON TELEVISI INDONESIA TAHUN 2008 - Darni (Lentera, Jurnal Studi Perempuan, 2008)
Abstract Research   results   have   shown   that   violence   that   victimizes   women characters in Indonesian TV sinetron is mostly in the the form of psychological abuse,  which  involves  both  men  and  women  as  the  abusers.  In  the  case  of polygamy that is often considered hurt leaving a strong psychological impact to women, there were three of ﬁve sinetron that were used as the research data,i.e. Suci,  Munajah  Cinta,  and  Cinta  Bunga.  In  spite  of  the  attempt  a  man  like  the character Atar to be fair and just to his wives, women are often the victims. One main reason of conﬂicts and violence between women is their unwillingness to share their husbands love with another woman. It is interesting to ﬁnd that, for the  sake  of  a  mans  love  or  worldly  privileges,  women  characters  are  abused by other women as reﬂected in those sinetron, with polygamy as the root of the violence. Two characters, Amelia and Wilda, for instance, plot a murder of their husbands other wife, respectively, in order to gain full control over the husband. Those events imply that polygamy has the potential to cause anxiety and violence to women.